Nonverbal communication in human interaction - Knapp, Mark L.; Hall, Judith A. (Wadsworth, Cencage Learning, 2014)
Offers an interdisciplinary approach to the study of nonverbal communication that shows how it affects a wide variety of academic interests. In this title, the theory and research comes from scholars with a wide variety of academic backgrounds, including communication, anthropology, counseling, psychology, psychiatry, and linguistics